ROLE OF AUTO- AND HETEROLOGOUS RIBONUCLEASE III FAMILY ENZYMES IN THE RESISTANCE TO PATHOGENS AND REGULATION OF GENE EXPRESSION IN HIGHER PLANTS - I. V. Zhirnov; E. A. Trifonova; A. V. Kochetov (Вавиловский журнал генетики и селекции)
The current view on the biological role of ribonuclease III family plant enzymes (Dicer-like dsRNAses) is considered. Emphasis is placed on their role in molecular mechanisms conferring resistance to pathogens.